The effect of mindfulness training prior to total joint arthroplasty on post-operative pain and physical function: study protocol for a randomised controlled trial - Dowsey, Michelle M (BioMed Central, 2014)
BACKGROUND: Osteoarthritis is a leading cause of disability in developed nations. In Australia it afflicts 16.5% of the adult population. Total joint arthroplasty is considered the treatment of choice for end stage osteoarthritis. The number of total joint arthroplasties undertaken in Australia has doubled over the last decade (more than 80,000 procedures in 2011). The incidence of pre-operative psychological distress in this group of patients is reported between 30% and 60% and pre-operative psychological distress is associated with poorer pain and functional outcomes after surgery. This study will use a mindfulness-based psychological intervention to enhance outcomes in people undergoing total joint arthroplasty and, in addition, will test hypotheses about coping with chronic illness in an aged population. This study is the first of its kind and will provide a greater understanding of the role of a mental health enhancement program on the physical recovery of total joint arthroplasty patients. METHODS/DESIGN: One hundred and fifty people with end-stage arthritis on the waiting list for total hip or knee arthroplasty will be recruited and randomly allocated to one of two groups using computer-generated block randomisation. A randomised controlled trial adhering to CONSORT guidelines will evaluate the efficacy of a mindfulness training program (weekly group-based classes in mindfulness practice, 2 ½ hours, for 8 weeks plus a 7-hour Saturday session in Week 6) prior to total joint arthroplasty, compared to a “standard care” group who will undergo routine total joint arthroplasty. Primary outcomes will be evaluated by a blinded examiner at baseline, 3 and 12 months post-surgery, using a validated self-reported pain and physical function scale. Secondary outcomes will include i) a range of validated measures of psychological wellbeing and ii) health economic analysis. All analyses will be conducted on an intention to treat basis using linear regression models. Health economic modelling will be applied to estimate the potential cost-effectiveness of mindfulness training and total joint arthroplasty. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry (ANZCTRN12611001184965). Date of registration; 15th November 2011.